2020
DOI: 10.1038/s41467-020-18649-5
|View full text |Cite|
|
Sign up to set email alerts
|

Abiraterone acetate preferentially enriches for the gut commensal Akkermansia muciniphila in castrate-resistant prostate cancer patients

Abstract: Abiraterone acetate (AA) is an inhibitor of androgen biosynthesis, though this cannot fully explain its efficacy against androgen-independent prostate cancer. Here, we demonstrate that androgen deprivation therapy depletes androgen-utilizing Corynebacterium spp. in prostate cancer patients and that oral AA further enriches for the health-associated commensal, Akkermansia muciniphila. Functional inferencing elucidates a coinciding increase in bacterial biosynthesis of vitamin K2 (an inhibitor of androgen depend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
56
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(63 citation statements)
references
References 62 publications
(79 reference statements)
2
56
0
Order By: Relevance
“…From a therapeutic perspective, Akkermansia muciniphila seems to be relevant for the activity of abiraterone acetate in patients with castrate-resistant prostate cancer. This bacterium triggers the bacterial biosynthesis of vitamin K2, which inhibits androgen-dependent tumor growth [ 52 ].…”
Section: Tumor-associated Microbiomementioning
confidence: 99%
“…From a therapeutic perspective, Akkermansia muciniphila seems to be relevant for the activity of abiraterone acetate in patients with castrate-resistant prostate cancer. This bacterium triggers the bacterial biosynthesis of vitamin K2, which inhibits androgen-dependent tumor growth [ 52 ].…”
Section: Tumor-associated Microbiomementioning
confidence: 99%
“…lactis LMG P-28149 improved the abundance of A. muciniphila associated with decreased glucose and insulin levels in obese mice (Alard et al 2016). Acetate and lactate derived from the probiotics might stimulate the growth of A. muciniphila because acetate and the acetate-conjugated portion of the drug could boost the growth of A. muciniphila (Daisley et al 2020). In a human study, the administration of L. rhamnosus HN001 and B. longum BB536 increases the abundance of A. muciniphila (Toscano et al 2017).…”
Section: Interaction With Bacteriamentioning
confidence: 99%
“…Orally administrated with Enterococcus hirae cause a restoration of CTX anti-tumor efficacy by inducing differentiation of TH17 and pathogenic TH17 cells, promoting tumor-specific Th1 and CTL activity (179). Abiraterone acetate is both an inhibitor of androgen biosynthesis and a highly effective drug of prostate cancer, which reduces the harmful microorganisms and promotes the growth of anticancer microorganisms through metabolizing the gut microbiota (180). Otherwise, Pushalkar et al suggested that bacterial ablation can reshape TME in the orthotopic mouse model of pancreatic cancer (PDAC), induce activation of T cell and increase the sensitivity of immunotherapy (181).…”
Section: Gut Microbiota Affect the Efficacy Of Cancer Immunotherapymentioning
confidence: 99%